Efektivitas Proses Hukum Acara Perdata dalam Penyelesaian Kasus Utang Piutang di Pengadilan Negeri - Cloudya, Barbara (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
In Indonesia, the effectiveness of the civil procedural law process in debt proceedings in the District Court is very important. This legal process seeks justice and legal certainty for the parties to a debt dispute. Civil procedural law regulates the actions of plaintiffs and defendants from the filing of a lawsuit to the execution of a judgment. Clear regulations should help parties understand their rights and responsibilities, making dispute resolution easier. With the growing complexity of economic relationships and the increasing number of debt and credit disputes, it is important to evaluate the effectiveness of the civil procedural law process in resolving these cases in the district courts. This article will discuss various aspects of the civil procedural law process, the challenges faced, as well as recommendations to improve the effectiveness of debt and credit dispute resolution.